The Investigation of Organic Binder Effect on Morphological Structure of Ceramic Membrane Support - Boussemghoune, Mohamed; Chikhi, Mustapha; Ozay, Yasin; Guler, Pelin; Unal, Bahar Ozbey; Dizge, Nadir (Mdpi, 2020)
In this study, we investigated the effect of different organic binders on the morphologic structure of ceramic membrane support. Natural raw clay material (kaolin) was used as the main mineral for ceramic membrane support. The physical and chemical properties of kaolin powder and the supports were identified by X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET), thermo gravimetric analysis (TGA), scanning electron microscopy (SEM), particle size and zeta potential distribution. Based on the XRF test, the main composition of kaolin powder was SiO2 (47.41%) and Al2O3 (38.91%), while the rest were impurities. The FTIR spectra showed the functional groups of Si-O and Al-O. The XRD diffractogram of natural raw clay powder identified kaolinite and nacrite were the main mineral phase whereas muscovite and quartz were detected in small quantities in the sample. After prepared the ceramic membrane supports, XRD diffractogram showed that anorthite and gehlenite were detected as the main mineral phases for ethylene glycol (EG), gelatin, methocel and for polyethylene glycol (PEG), respectively. According to BET analyses, the maximum and the minimum pore width were obtained for PEG and gelatin organic binders.
Keywords: organic binder; natural clay; kaolin; ceramic support; characterization